Sensitivity of Urinary Tract Infection E. coli to Amoxicillin, Ciprofloxacin, Cefotaxime, and Ceftriaxone in Tarhuna City (Comprehensive Journal of Science, 2025)
A cross-sectional study was conducted to determine the antibiotic susceptibility of E. coli isolates from 130 patients (both genders) presenting with urinary tract infections (UTIs). The study employed standard microbiological techniques for pathogen isolation and identification, including growth on MacConkey agar and confirmation with the API 20E system. The Kirby-Bauer disc diffusion method was used to assess the susceptibility of the isolates to various antibiotics. Results showed an alarmingly high rate of resistance to commonly prescribed antibiotics. Of the isolates, only 45 were sensitive to Amoxicillin (34.6%), while 6 were sensitive to Ciprofloxacin (4.6%). The findings indicate that the efficacy of these first-line agents for the empirical treatment of UTIs has been significantly compromised in the studied population. This highlights a critical need for updated treatment guidelines and robust antibiotic stewardship to combat the growing public health threat of antibiotic resistance.
Keywords: antibiotic, susceptibility, E. coli , MacConkey, API 20E, disc diffusion